Assessments of the Effect of Increasingly Severe Cathodic Pretreatments on the Electrochemical Activity of Polycrystalline Boron-Doped Diamond Electrodes - Brocenschi, Ricardo F.; Hammer, Peter [UNESP]; Deslouis, Claude; Rocha-Filho, Romeu C. (American Chemical Society (ACS), 2016)
The electrochemical response of many redox species on boron-doped diamond (BDD) electrodes can be strongly dependent on the type of chemical termination on their surface, hydrogen (HT-BDD) or oxygen (OT-BDD). For instance, on an HT-BDD electrode the [Fe(CN)6]3-/4- redox system presents a reversible voltammetric behavior, whereas the oxidation overpotential of ascorbic acid (AA) is significantly decreased. Moreover, the electrochemical activity of BDD electrodes can be significantly affected by electrochemical pretreatments, with cathodic pretreatments (CPTs) leading to redox behaviors associated with HT-BDD. Here we report on the effect of increasingly severe CPTs on the electrochemical activity of a highly doped BDD electrode, assessed with the [Fe(CN)6]3-/4- and AA redox probes, and on the atomic bonding structure on the BDD surface, assessed by XPS. The hydrogenation level of the BDD surface was increased by CPTs, leading to decreases of the total relative level of oxidation of the BDD surface of up to 36%. Contrary to what is commonly assumed, we show that BDD surfaces do not need to be highly hydrogenated to ensure that a reversible voltammetric behavior is obtained for Fe(CN)6]3-/4-; after a CPT, this was attained even when the total relative level of oxidation on the BDD surface was about 15%. At the same time, the overpotential for AA oxidation was confirmed as being very sensitive to the level of oxidation of the BDD surface, a behavior that might allow the use of AA as a secondary indicator of the relative atomic bonding structure on the BDD surface.